Optimized Preparation of Levofloxacin Loaded Polymeric Nanoparticles - Manuel López-López; Angela Fernández-Delgado; María Luisa Moyá; Daniel Blanco-Arévalo; Cecilio Carrera; Rafael R. de la Haba; Antonio Ventosa; Eva Bernal; Pilar López-Cornejo (MDPI AG, 2019)
In this work, poly(lactic-co-glycolic acid) (PLGA) and chitosan (CS) nanoparticles were synthesized with the purpose of encapsulating levofloxacin (LEV). A thorough study has been carried out in order to optimize the preparation of LEV-loaded polymeric nanoparticles (NPs) suitable for parenteral administration. Changes in the preparation method, in the organic solvent nature, in the pH of the aqueous phase, or in the temperature were investigated. To the authors´ knowledge, a systematic study in order to improve the LEV nanocarrier characteristics and the yield of drug encapsulation has not been carried out to date. The physicochemical characterization of the NPs, their encapsulation efficiency (EE), and the in vitro release of LEV revealed that the best formulation was the emulsion-solvent evaporation method using dichloromethane as organic solvent, which renders suitable LEV loaded PLGA NPs. The morphology of these NPs was investigated using TEM. Their antimicrobial activities against several microorganisms were determined in vitro measuring the minimum inhibitory concentration (MIC). The results show that the use of these loaded LEV PLGA nanoparticles has the advantage of the slow release of the antibiotic, which would permit an increase in the time period between administrations as well as to decrease the side effects of the drug.